A highly selective fluorescence sensor for cysteine/homocysteine and its application in bioimaging1. Issue 36 (23rd April 2015) - Liu, Tao; Huo, Fangjun; Yin, Caixia; Li, JianFang; Niu, Lixi
<x xml:space="preserve">Abstract</x> A new near-infrared (NIR) sensitive Cys/Hcy probe based on squaraine was rationally designed and synthesized.